Designing a combined device for determining the place of arc discharge - Parkhomenko, Roman; Aniskov Оlexandr; Tsibulevsky, Yuri; Melnik, Olga; Shchokina, Olga; Kharitonov, Alexander; Kryvenko, Oleksii; Omelchenko, Oleksandr; Chorna, Viktoriia; Tsvirkun, Sergij (Eastern-European Journal of Enterprise Technologies, 2018)
We determined factors that arise during an arc discharge and detected possibility of their use to accelerate protection against arc closure. This enables creation of a combined device for accurate determination of an arc discharge. In particular, we can expand the spectrum of sensitivity of an optical sensor by the use of ultraviolet radiation without its replacement. We considered possibility of acceleration of response of protection against arc closure operation due to refusal of its blocking with relay circuits for maximum current protection and reduction of an influence of solar radiation on operation of PAC (protection against arc closure). We substantiated possibility of development of a more advanced device for protection against arc circuits, which gives possibility to expand the spectrum of the optical sensor in the region of ultraviolet radiation. We proposed the solution of the problem of increasing of sensitivity of protection against arc closure. This is possible by converting the ultraviolet radiation into a visible part of the optical spectrum, which will expand the spectrum of sensitivity of the optical sensor to the region of ultraviolet radiation and, accordingly, increase its sensitivity. This is due to the fact that 70 % of an arc discharge radiation falls on the ultraviolet region and only 15 % on the visible and infrared spectra of the optical radiation. The obtained results give grounds to assert about possibility of realization of a device of combined protection for determination of arc circuits in industrial production, as well as expansion of spectral sensitivity of optical sensors. In addition, we developed a combined device for determination of an arc discharge through a use of an ultrasound system. Known developments devoted to determination of location of an arc discharge by comparing intensity of a signal from a flash at both ends of the ten-meter optical light conductor are characterized by the fact that the maximum difference between the arrival time of signals from a flash point to sensors at the ends of the optical fibers is 5ns. This is a very low temporal level compared to the light conductor length at the velocity of 300,000 km/s. The system proposed in this study uses the sound velocity, which reaches 342/s, to determine an arc discharge, which simplifies a time measurement device for determination of a short circuit greatly and increases accuracy of time measurement by three orders of magnitude (103).